PENGEMBANGAN SOAL LATIHAN AKM BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN LITERASI MEMBACA SISWA KELAS V SD - Devky Diptya Nararyani, - (2022)
ABSTRACT DEVELOPMENT OF LOCAL WISDOM-BASED AKM EXERCISE QUESTIONS TO IMPROVE READING LITERACY FOR 5TH GRADE ELEMENTARY SCHOOL STUDENTS By Devky Diptya Nararyani 1800712 AKM is one of the government's ways to improve the literacy quality of students in participating in the PISA program. Therefore, the purpose of this study is to describe how the development design and results of developing AKM practice questions based on local wisdom are to improve the literacy of fifth grade elementary school students. The research method used is a qualitative approach and ADDIE model design. The location of this research is SDN Tanah Baru, Cirebon City. The trial was conducted by 20 fifth grade students as research subjects. Data collection techniques through interviews and using three methods of data analysis, namely 1) Content validity test involving three experts (material, language, and evaluation experts. 2) Empirical validity test using SPSS Statistic 22. 3) Reliability test using SPSS Statistic 22. The results of this study are: 1) The design of developing AKM practice questions based on local wisdom totaling 30 items containing informational text content and fiction texts adapted to cognitive processes, competencies, and the context of AKM questions. 2) The results of developing the content validity test questions of the second round -1 material expert = 95% linguists = 61.5% evaluation = 91.6% and the second round of linguists = 90.4% so it can be said that it is valid. Then the empirical validity test of the correlation between 30 items with a total score showed 24 of the 30 items were declared valid, but the other 6 questions were invalid. The results of the discriminatory power test of 30 items have a range of 0.70-1.00 so they have excellent discriminating power. The reliability test showed the reliability coefficient of 30 items from the test results obtained rca = 0.976 so that the reliability was very high. Keywords: AKM, Local Wisdom, Reading Literacy